Exploring Perceptions and Health Awareness in Fish Consumption Across Coastal and Inland Kerala - Sajeev, M V; Joshy, C G (Indian Journal of Extension Education, 2024)
The study investigated fish consumption patterns and consumer perceptions in Kerala, focusing on coastal and inland districts during 2020. Using a sample of 396 households from four districts and employing suitable tests, the study reveals significant disparities in monthly and per capita fish consumption, with coastal areas displaying higher rates. The majority of consumers hold a moderate perception of nutritional and health benefits, indicating a need for targeted health awareness programs. Coastal and inland consumers differ significantly in their perceptions, with coastal residents demonstrating greater awareness of dietary advantages, while inland consumers express resignation to lower quality due to supply chain limitations. Urban consumers exhibit an optimistic health perception, contrasting with rural concerns about certification systems and government inefficiencies in ensuring safe fish. The study emphasizes the necessity for customized information dissemination and awareness programs to address the diverse concerns of fish consumers in Kerala.
Keywords: Fish consumption; Consumers; Perception; Coastal; Inland; Rural; Urban; Kerala